Long-Term Scenario of International Developments - A. I. Podberezkin; M. V. Kharkevich (Vestnik MGIMO-Universiteta)
This paper proposes an approach to long-term scenario building in international relations, based on the analysis of changes in the dialectics of war and peace. Long-term trends in the development of forms and manifestations of violence in international relations, as well as the methods and approaches to its control and management determines the development of international relations. In solving the methodological problem of long-term forecasting, it must be as-sumed that the mere mechanical extrapolation even in the medium term has no meaning. The key current trend in terms of political violence is a blurring of the distinction between war and peace. This trend can be described as networking of war. Network war theory is a model of military strategy in the context of postmodernism. As a model of the new economy based on information and high technologies demonstrates its superiority over traditional capitalist and socialist models of the industrial age, and network war claims qualitative superiority over previous strategic concept of the industrial era. In modern political networks violent and non-violent instruments of influence co-exist in undifferentiated form. Network politics becomes total. Victory in the network war is the fact that the opponent should become part of the network. Since the network is formed around shared values, the network war can be reduced to a war of values. The clash between the networks will most likely wear un-compromising nature, so that in the end there will be only one network. Uncompromising network war is like the uncompromising religious wars and clashes of civilizations.